THE EFFECT OF CELEBRITY ENDORSER CREDIBILITY AND BRAND IMAGE ON PURCHASE INTENTION MODERATED BY BRAND DIFFERENCE - Evi Novitasari; Nabila Kharimah Vedy; Sri Rahayu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Social media offers many opportunities for online marketing strategies that harness the power of society, especially when they are combined with traditional approaches such as celebrity endorsements. The reach, frequency, and speed of communication on social media offer the ideal range for online marketing delivery. However, the speed of change could threaten to short-lived the effects of investing in social media marketing. The shift in behavior from offline (offline) to online ( online) in Indonesian society has opened up new opportunities in online shops . One that uses an online shop system is the cosmetic brand Oriflame, by attracting market share, one of which is through social media Facebook. For example, the cosmetic product "The One" from Oriflame uses a celebrity endorser, namely Isyana Sarasvati. This type of research is a causality research design with a quantitative approach. The research population is prospective consumers and members of Oriflame throughout Indonesia. Sampling with non-probability sampling method using the sampling technique Purposi v e Sampling to suit the research objectives, and the population in the study is potential consumers. Data collection techniques by distributing online questionnaires using google form as many as 220 respondents who have been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study indicate that the biggest influence is on the brand image variable on purchase intention, while the smallest influence is the celebrity endorser credibility variable on purchase intention. As well as brand differentiation which has a positive influence, and is able to increase the influence between celebrity endorser credibility and brand image on purchase intention. Keywords: Celebrity Endorser Credibility, Brand Image, Brand Differentiation, Purchase Intention